Lung Metastases to the Heart with Atypical Clinical Manifestations of Cardiac Failure - Natalia HYRIAVENKO; Vladyslav SIKORA; Wireko Andrew AWUAH; Toufik ABDUL-RAHMAN; Mykola LYNDIN; Anatolii ROMANIUK (Medeniyet Medical Journal)
The heart is a rare site of cancer metastases, even from the most common malignancies, such as lung cancer. Cardiac metastases may lead to myocardial dysfunction. This report presents a case of lung cancer metastases to the left ventricular myocardium that clinically manifested as atypical symptoms of cardiac dysfunction. The metastases were not revealed until after the patient died. Posthumously, the anamnesis, autopsy results, and morphological examination were evaluated. We demonstrated that the atypical symptoms of cardiac dysfunction were caused by occult (undiagnosed) metastases of lung cancer cells to the heart. The doctors did not consider this variant as possible metastatic lung cancer, because the patient had been treated radically one year earlier.